Solomon Islands : First Review Under the Standby Credit Facility and Request for Modification of Performance Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Solomon Islands. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The First Review Under the Standby Credit Facility (SCF) discusses Solomon Islands' satisfactory performance under the SCF-supported program, approved in December 2011. The current arrangement is intended to be precautionary and, given the current level of reserves, the authorities do not intend to draw on the IMF's resources unless an unexpected need arises. The outlook remains favorable, but with large near-term downside risks. Substantial progress has been made toward implementing structural benchmarks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet